A model study of Saharan dust emissions and distributions during the SAMUM-1 campaign - Laurent, B.; Tegen, I.; Heinold, B.; Schepanski, K.; Weinzierl, Bernadett; Esselborn, M. (Journal of Geophysical Research, 2010)
Simulations of Saharan dust emission, transport, and deposition are performed using new developments of the regional model COSMO-MUSCAT for the Saharan Mineral Dust Experiment (SAMUM-1), which took place in MayÃ¢ÂÂJune 2006. Up-to-date surface soil data sets developed especially to model dust emissions are used, and a new representation of the dust size distribution is proposed. Compared with previous model studies performed with COSMO-MUSCAT, the advantage of our approach is that no tuning factor on the erosion threshold is needed for the whole Sahara. The performances and limitations of COSMO-MUSCAT to model the regional dust cycle are discussed. The spatiotemporal variability of simulated Saharan emissions is evaluated using a backtracking approach to locate dust sources with Meteosat Second Generation (MSG) infrared difference images and using dust observations of North African meteorological stations. The Saharan dust emissions are estimated to be 78 Tg during the studied period. The model dust size distributions agree well with SAMUM-1 airborne measurements, previous model simulations, and Aerosol Robotic Network (AERONET) inversion products. Our ability to simulate the vertical cross section of a dust plume is also discussed with regard to airborne lidar measurements and former simulations. The horizontal distribution of model-derived aerosol optical thicknesses (AOT) is compared with Aqua-MODIS Deep Blue AOT and Ozone Monitoring Instrument (OMI) aerosol indexes. Dry and wet deposition rates are simulated. About 67% of the emitted dust is deposited in the vicinity of the emitted source areas over North Africa and close marine areas, and 33% is transported out of the studied area toward other continents and remote ocean areas.